Bulk single crystals of β-Ga2O3 and Ga-based spinels as ultra-wide bandgap transparent semiconducting oxides. Issue 1 (February 2021) - Galazka, Zbigniew; Ganschow, Steffen; Irmscher, Klaus; Klimm, Detlef; Albrecht, Martin; Schewski, Robert; Pietsch, Mike; Schulz, Tobias; Dittmar, Andrea; Kwasniewski, Albert; Grueneberg, Raimund; Anooz, Saud Bin; et al.
Abstract: In the course of development of transparent semiconducting oxides (TSOs) we compare the growth and basic physical properties bulk single crystals of ultra-wide bandgap (UWBG) TSOs, namely β-Ga2 O3 and Ga-based spinels MgGa2 O4, ZnGa2 O4, and Zn1-x Mgx Ga2 O4 . High melting points of the materials of about 1800 -1930 °C and their thermal instability, including incongruent decomposition of Ga-based spinels, require additional tools to obtain large crystal volume of high structural quality that can be used for electronic and optoelectronic devices. Bulk β-Ga2 O3 single crystals were grown by the Czochralski method with a diameter up to 2 inch, while the Ga-based spinel single crystals either by the Czochralski, Kyropoulos-like, or vertical gradient freeze / Bridgman methods with a volume of several to over a dozen cm 3 . The UWBG TSOs discussed here have optical bandgaps of about 4.6 - 5 eV and great transparency in the UV / visible spectrum. The materials can be obtained as electrical insulators, n -type semiconductors, or n -type degenerate semiconductors. The free electron concentration ( ne ) of bulk β-Ga2 O3 crystals can be tuned within three orders of magnitude 10 16 - 10 19 cm −3 with a maximum Hall electron mobility ( μ ) of 160 cm 2 V −1 s −1, that gradually decreases with ne . In the case of the bulk Ga-based spinel crystals with no intentional doping, the maximum of ne and μ increase with decreasing the Mg content in the compound and reach values of about 10 20 cm −3 and about 100 cm 2 V −1 s −1 (at ne > 10 19 cm −3 ), respectively, for pure ZnGa2 O4 .